ANALISIS PENGARUH PERPUTARAN MODAL KERJA, STRUKTUR MODAL DAN SKALA PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Chaerunnisa Rumianti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aimed to analyze the effect of the rate of turnover of working capital, capital structure and scale of the company to profitability in automotive companies. The population of this research are automotive companies listed in Indonesia Stock Exchange in 2014-2016 amounted to 17 companies. The sampling method used is purposive sampling and acquired 12 companies in the sample. The method of analysis which is used is multiple regression analysis using SPSS software. Based on the results of the partial or t test, variable working capital turnover rate had no significant effect on profitability, capital structure variable has no significant effect on profitability as well as the scale of the company has no significant effect on profitability. Thus the three independent variable has no significant effect on the dependent variable.